The L1 as a consciousness-raising tool in learning L2 grammar - Wach, Aleksandra (Wydawnictwo Naukowe UAM, 2019)
The main aim of the book is to investigate the facilitative role of learners’ native language (L1) in raising their consciousness of foreign language (L2) grammatical structures. The literature review focuses on selected second language acquisition theories which explain the role of the different conceptualizations of consciousness in L2 learning, on the position of grammar in contemporary L2 pedagogy, with special regard to grammatical consciousness-raising, and on theoretical and empirical perspectives on the functions of learners’ L1 in L2 learning and teaching. The empirical part of the book presents the methodology and results of a mixed-methods study conducted on low-proficiency adult learners of L2 English with the aim of exploring the role of their L1 (Polish) in promoting the noticing, understanding, and explicit knowledge of L2 grammatical structures. The results revealed a number of significant functions of the L1 in enhancing the participants’ consciousness of the targeted structures, evidenced in the use of mental strategies (i.e. translation, cross-linguistic comparisons, making inferences, metalinguistic reasoning, etc.), in the results of tests, and in opinions expressed in debriefing interviews.
This book aims to explore the important consciousness-raising function of learners’ native language (L1) in learning foreign language (L2) grammar. The literature review contains a detailed elaboration on the following topics: • theoretical and empirical perspectives on consciousness in SLA, • grammar as a component of instructed L2 acquisition, • consciousness-raising as an option in the teaching of L2 grammar, • the position of learners’ L1 in L2 learning and teaching, • methodological concerns in researching consciousness-related concepts in SLA. The mixed-methods study reported in this work addressed the role of the L1 (Polish) in learning L2 (English) grammatical structures. To this end, both the learning-as-process and learning-as-product orientations were embraced in the investigation, resulting in a comprehensive account of the L1 as a consciousness-raising tool in the instructed acquisition of L2 grammar. Integrating theoretical, pedagogical, and empirical perspectives on consciousness, grammar, and the L1 in L2 learning and teaching, the book may be of interest to a wide audience, especially L2 teachers, philology students, and SLA and ELT researchers.
Keywords: consciousness-raising; grammar; English as a foreign language; EFL; L1; native language; think-aloud protocol